'Womb for work' experiences of Thai women and gestational surrogacy practice in Thailand. (20th October 2022) - Attawet, Jutharat; Wang, Alex; Sullivan, Elizabeth
Abstract: Risks to gestational surrogates became a concern for public health. In commercial gestational surrogacy arrangements, gestational surrogates are commonly recruited from low- to middle-income countries. Thailand is well known as a surrogacy hub in this regard. However, little is known concerning Thai surrogacy practice and the risks that Thai gestational surrogates experiences. The semi-structured interviews with fifteen Thai women who had been gestational surrogates were conducted over the telephone in Thai between March and May 2020 and lasted approximately 30 minutes. Thematic analysis was applied to analyse the translated interviews. The findings indicated that 'womb for work' was perceived as a surrogacy career among Thai women. 'Womb for work' was defined as a superordinate theme that consisted of three subthemes: (i) gestational surrogacy arrangements in Thailand; (ii) the business model of gestational surrogacy arrangements in Thailand; and (iii) risk experiences of gestational surrogates. Clear deficiencies in surrogacy practice and regulations were identified, which put gestational surrogates at risk, including those associated with embryo transfer, transnational gestational surrogacy, and unsupported pregnancies. This study shows the urgent need to introduce regulations to protect women's health transnationally in this domain more effectively.